Description of a new species and complementary description of a known species of Iphiseiodes de Leon (Acari: Phytoseiidae) - De Carvalho Mineiro, Jeferson Luiz; Martins Gomes de Castro, Tatiane Marie [UNESP]; De Moraes, Gilberto Jose (Magnolia Press, 2011)
Species of Iphiseiodes de Leon have been reported only from tropical and subtropical regions of the Americas. In this paper, a new species of this genus is described from southeastern Brazil and a complementary description is provided for Iphiseiodes saopaulus (Denmark & Muma).
Keywords: Acari; predatory mite; Taxonomy; Biological control